Governance and Practices Related to Environmental Risk Management in the Metropolitan Regions of São Paulo: Evidence from the Municipal Index of Protected Cities (i-Cidade) of the Municipal Management Effectiveness Index (IEG-M) - Gomes, Erasmo (Scientific Journal ANAP, 2025)
Objective - This study aims to analyze the implementation of the i-CIDADE dimension of the Municipal Management Effectiveness Index (IEG-M) in the Metropolitan Regions of the State of São Paulo, focusing on civil defense actions, risk management, and urban resilience. It seeks to identify advances, gaps, and disparities in the institutionalization of local public policies aimed at protecting the population in the face of adverse events. Methodology - This is a descriptive and quantitative study based on documentary analysis of the IEG-M data from the 2023 cycle, supplemented by charts and interpretations drawn from official indicators and institutional normative frameworks. The methodology includes cross-referencing data from different dimensions of the index, with emphasis on the items that make up the i-CIDADE dimension. Originality/relevance - The study contributes to filling a gap in national literature by providing an updated diagnosis of the status of civil protection and defense policies in metropolitan municipalities of São Paulo. It stands out for articulating technical data from external control bodies with discussions on urban governance and resilience—topics of growing relevance in the context of climate change and increasing frequency of extreme events. Results - The results show progress in the creation of civil defense coordinators and in the adherence to international programs such as MCR2030. However, weaknesses are identified in the use of contingency plans and in conducting simulated drills. There is significant variation across regions, with positive highlights for Campinas, Jundiaí, and São Paulo, and critical performance in Ribeirão Preto and São José do Rio Preto. Theoretical/methodological contributions - The study offers methodological inputs for comparative analyses between municipalities and proposes objective criteria for monitoring the effectiveness of risk management. It contributes to the field of institutional evaluation and metropolitan public policies by proposing indicators that link urban planning, risk management, and a prevention-oriented institutional culture. Social and environmental contributions - The findings reinforce the importance of public policies aimed at reducing social and environmental vulnerabilities, pointing to pathways for strengthening a culture of prevention and urban resilience, with direct impacts on the safety, well-being, and quality of life of at-risk populations.